Utilization of NDMI Method in Landsat 8 Satellite Imagery for Analysis of Multi-Hazard Susceptibility - Suyeda, Fadhil D.; Setiawan, Budhi (GMPI Conference Series, 2022)
Liquefaction and landslide can occur during earthquakes caused by changes in soil saturation levels so that the soil loses strength due to loss of tension between grains. One of the determinations of soil moisture data using satellite imagery analysis is Landsat. Landsat has provided moderate, global, synoptic spatial resolution and repeated earth's soil surface coverage. This paper discusses the multi-hazard susceptibility using Landsat-8 satellite imagery with a combination of NDMI (Normalized Difference Moisture Index) ratio bands in Sunurraya Village and Simpang Saga Village, South OKU Regency, South Sumatra. The combination of NDMI bands determines the spread of soil saturation levels and differences in moisture in vegetation conditions. Other supporting data are soil's physical properties, including water content, density, hydrometer analysis, and Atterberg limits analysis. Overlay of NDMI data analysis and soil test analysis shows the level of liquidation insecurity in the research area on a regional and local scale